2004
DOI: 10.1021/ie049825y
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics of Maleated Polypropylene/Clay Hybrids

Abstract: The isothermal crystallization kinetics of maleic anhydride grafted polypropylene (mPP) in hybrids with unmodified or organically modified montmorillonite (MMT), which have been prepared by melt intercalation in a mixer, has been investigated by using time-resolved wideangle X-ray scattering (WAXS) and differential scanning calorimetry (DSC). WAXS and transmission electron microscopy (TEM) showed that the mPP/unmodified MMT hybrids formed macrophase-separated mixtures rather than intercalated nanocomposites, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 36 publications
3
32
0
1
Order By: Relevance
“…The higher level of nanoparticle inclusion was noted to yield retardation of crystallization due to diffusion constraints. This was also apparent in a study where unmodified and organically modified clay were incorporated in maleic anhydride grafted polypropylene [25]. Nucleation was observed with unmodified clay, whereas the exfoliated clay yielded a reduced crystallization rate.…”
Section: Fundamental Considerationsmentioning
confidence: 73%
“…The higher level of nanoparticle inclusion was noted to yield retardation of crystallization due to diffusion constraints. This was also apparent in a study where unmodified and organically modified clay were incorporated in maleic anhydride grafted polypropylene [25]. Nucleation was observed with unmodified clay, whereas the exfoliated clay yielded a reduced crystallization rate.…”
Section: Fundamental Considerationsmentioning
confidence: 73%
“…It has been reported that, in nanocomposites prepared with organoclay (Cloisite 20A), the β ‐crystalline fraction is suppressed in nanocomposites with MAH‐ graft ‐PP (Polybond 3200) as an additive 52,53. There appears to be no β ‐crystalline fraction in annealed MAH‐ graft ‐PP composites based on Cloisite Na + or Cloisite 20A 54. A PP nanocomposite prepared with Nanofil 948, a clay nominally similar to Cloisite 20A, has a significant β ‐crystalline fraction (Figure 8) which again was reduced in compositions containing the nonionic surfactant 1d .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 and Table 1 show that the crystallization temperature is increased by 11 to 18 °C in the composites as compared to PP, depending on the type and concentration of CNT, and a notable increase of X c can be observed for 3 wt.% loaded materials. The ability of fillers to increase PP crystallization temperature is known for talc [16] and for nanoclays [19,20] and is generally attributed to the particle dimensions and dispersion degree. As far as carbon nano fibres are concerned, Lozano et al [6] observed an increase in T c and in X c by increasing the carbon nanofibres content in a PP matrix up to a limiting value.…”
Section: Thermal Behaviourmentioning
confidence: 99%